Indicator of the Succession Stages of Forest Fragments of the Atlantic Forest Biome - Amorim, Amanda Trindade [UNESP]; de Sousa, Jocy Ana Paixão [UNESP]; Lourenço, Roberto Wagner [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2019)
Studies on the succession stages of forest fragments are essential for their preservation and conservation, as well as contributing significantly to the management and planning aimed at recovering their biodiversity. However, the evaluation of these stages demands high costs, qualified personnel and time, especially in the fieldwork. Therefore, research has emerged incorporating methods that use geoprocessing techniques for evaluations of this nature. The objective of this research was to study the parameters that interfere in the dynamics of the forest fragments and the biophysical characteristics, whose purpose was to propose an indicator of the succession stages of forest fragments of the Atlantic Forest biome. To this was used as the basis the Murundú-Paiol watershed located in the southeast of the state of São Paulo. The methods were based on the study of the factors that interfere in the dynamics of forest fragments (size, anthropic effect around, altitude, relief and sun exposure) and vegetation indices, generated from geoprocessing techniques. All these factors were correlated and the forest fragments were selected for evaluation in the field. Among all the parameters evaluated, only those related to altitude and relief showed a good correlation with the vegetation indices, being these the integrating parameters in the indicator of the succession stages. This indicator showed an accuracy of 85.7% in the evaluation, which allows to be replicated in other similar studies, presenting as a viable scientific alternative and capable of indicating the probable succession stage of the forest fragments.
Indicador dos Estágios de Sucessão de Fragmentos Florestais do Bioma Mata Atlântica
Keywords: Forest resource; Geoprocessing; Mathematical modeling